EFEKTIVITAS IMPLEMENTASI FINGER PRINT DALAM MENINGKATKAN KEDISIPLINAN PEGAWAI DI UPT PUSKESMAS RAWAT INAP KECAMATAN MANDREHE KABUPATEN NIAS BARAT - Berkatone Waruwu; Eliagus Telaumbanua; Robin Markus Putra Waruwu; Palindungan Lahagu (Jurnal Publikasi Manajemen Informatika, 2026)
This research is titled The Effectiveness of Fingerprint Implementation in Improving Employee Discipline at the Inpatient Health Center (UPT Puskesmas) of Mandrehe Subdistrict, West Nias Regency. The aim of this study is to examine how the fingerprint system is implemented within the health center, to what extent it contributes to improving employee discipline, performance, and service delivery, and to identify the challenges encountered during its implementation. This study employs a qualitative approach with data collected through interviews, observations, and documentation. The results reveal that the fingerprint system has been implemented in accordance with established procedures and has had a positive impact on employee discipline, particularly in terms of attendance and punctuality. Furthermore, it has encouraged greater individual responsibility in carrying out public service duties. However, several challenges were identified, such as technical issues with the fingerprint device, limited technical understanding among some employees, and inadequate supporting infrastructure.